Heterogeneric Diversity and Richness of Avifauna in a Degraded Landscape of Arial Beel in Bangladesh (Jagannath University Journal of Life and Earth Sciences, 2024)
Bird diversity and richness reflect the habitat quality of ecosystems. The species composition, diversity, and richness of birds were studied at Shologhar Union, a degraded landscape of Arial Beel, from March 2016 to February 2017, using line transect and point count methods. A total of 75 species of birds belonging to 14 orders and 35 families were recorded; most of them were residents (83%). Non-passerine birds were predominant (40 species, 53% of total species), with 18 families and 38 genera. Only one near-threatened species (Yellow Wattled Lapwing Vanellus malabaricus) was recorded. Among resident birds, Baya weaver (Ploceus philippinus) was dominant, and the Yellow Wagtail (Motacilla flava) was predominant among migratory birds. Most species were terrestrial (51 spp., 68% of total birds), contributing only 23% of the population. The individual rarefaction revealed the highest species richness in March and the lowest in May and June. The highest population was recorded in winter (38%), and insectivore species (40%) were the highest. No significant seasonal variation occurred in the richness of birds (Kruskal-Wallis test: K = 0.05 df = 2, p = 0.971) and in different feeding guilds (Kruskal-Wallis test: K = 0.86, df = 5, p = 0.65). Ardeidae and Sturnidae represented the highest diversified families (6 species in each, RDi = 8), and Baya Weaver contributed the highest (26%) population. The presence of different species of birds suggests that this site could provide a suitable habitat for wild birds, and restoration management of this part of Arial Beel should require conserving the habitat of avifauna.Jagannath University Journal of Life and Earth Sciences, 9(1): 19-44, 2023 (June)